Obtenção de um híbrido de sílica e colágeno pelo processo sol-gel visando regeneração óssea - Paula, Julia Helena de (Universidade Federal de São Carlos, 2023)
The bone regeneration materials exploring is constantly increasing due to the lesions from traumas, illness and aging, that can cause serious complications and functionality loss. Biomaterials are used in order to stimulate bone tissue formation, improve bone healing and restructure tissues around the implants. The sol-gel process is a material synthesis technique promoted by the hydrolysis and condensation reactions of inorganic precursors in aqueous solution and it can be effective method for obtaining biomaterials. Thus, the main of this study was to synthesize silica hybrids containing collagen and triethyl citrate (TEC), through the sol-gel process, followed by the addition of simvastatin (SIN), looking for a material with suitable physical and chemical properties for bone regeneration. Furthermore, this system through the sol-gel process has not been reported in the literature yet. Therefore, the silica hybrids containing variations of 2%, 5% and 8% of collagen were characterized by Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TG), differential scanning calorimetry (DSC), assay amplitude mechanics, X-ray diffraction (XRD) and scanning electron microscopy (SEM). Macroscopically and through the SEM images it was verified the presence of different concentrations of collagen that interfered in the morphological distribution of the silica hybrids, where irregularities and heterogeneity on the surface of the hybrids was observed, moreover in the sample containing 2% of collagen. TEC contributed to the thermal degradation occurring at higher temperatures and its incorporation was confirmed by FTIR spectra, however the amorphous character of the silica xerogel was not modified even after this incorporation. Collagen also influenced the thermal stability of the hybrids, at higher concentrations greater thermal stability was observed. Collagen dispersive fibers influenced the lack of homogeneity and regularities, which were proven through the DSC curves, mechanical test of mechanics and SEM. The addition of SIN was performed on the silica hybrid with better thermal and mechanical properties, which contained 8% collagen. This drug was completely released in the initial minutes of the controlled release test, and it was not possible to define a release profile. However, the assay was influenced by collagen absorption at the same wavelength selected for the analysis and the released SIN concentration values were extrapolated. Therefore, silica hybrids containing collagen and SIN can be applied in low mechanical strength regions, such as in bone defects, injuries, wear and in fillings as an osteoinducer. Periodontitis, an oral disease that leads to loss of bone mass, is an application suggested.
Obtaining a silica-collagen hybrid via sol-gel process for bone regeneration
Keywords: Processo sol-gel; Colágeno; Regeneração óssea; Trietil-citrato; Sol-gel process; Collagen; Bone regeneration; Triethyl-citrate; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::CINETICA QUIMICA E CATALISE; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::QUIMICA TEORICA; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::POLIMEROS, APLICACOES